Assessment of the extent of practice and need for training in regional anesthesia among anesthesiologists in Saudi Arabia (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Objective The purpose of this survey was to evaluate Saudi Arabian anesthesiologists' levelof practice necessity of further training in regional anesthesia in 2015. Methods We used a surveyadministered via the internet to learn more about regional anesthetic use among the 400anesthesiologists who presented at the two annual meetings of the Saudi Anesthetic Association.Concerns included the application of ultrasound guidance, the use of regional anesthetic, necessity oftraining workshops. Findings Of the anesthetists surveyed, 55.2 responded. The majority of theseprofessionals were men, with a mean age of 25 to 50. The majority of anesthesiologists (81) often usedregional anesthetic in operating rooms (68.6) as opposed to designated block rooms. Only 12.7 of therespondents completed a fellowship in regional anesthesia, but 5.5 had formal training 81 wereeager to attend workshops on the subject. The institutional positions of the ultrasound users theircorrelation with ultrasound (r=-0.191) were significantly correlated negatively (P=0.026). Conclusions Wefeel that more could be done to enhance the Kingdom of Saudi Arabia's use of regional anesthesia, suchas instituting formal training and holding more regular, specialized seminars and courses on the subject,using ultrasound-guided regional anesthetic blocking techniques as the primary focus.